Understanding the impact of developmental coordination disorder on Belgian children and families: A national survey study - Amy De Roubaix; Griet Warlop; Dorine Van Dyck; Delphine Van Crombrugge; Silke Van den Abbeele; Melissa Licari; Hilde Van Waelvelde; Lynn Bar-On (PLoS ONE, 2025)
Background Developmental Coordination Disorder (DCD) is an under-recognized and often trivialized neurodevelopmental condition impacting five to six percent of children. This study aimed to map the impact of DCD on children and their families in Belgium. Methods The Australian ‘Impact for DCD’ questionnaire was translated and adapted to suit the Belgian context. Parents of 4-to-18-year-old children living in Belgium with movement difficulties consistent with DCD were invited to complete the online survey covering diagnosis, activities, school, therapy, and social and emotional impact. Results A total of 491 children were included in the analyses. First concerns emerged primarily at home (61.4%) at age 3.3 ± 2.25y, with help sought at age 4.7 ± 2.57y. Formal diagnosis occurred at age 6.9 ± 2.36y, with DCD (76.5%) and/or dyspraxia (38.4%) the most frequently received terms. DCD was generally unknown, especially within school settings. Nearly one in four children (23.2%) repeated a year of school. Reduced sleep quality (50.6%), fatigue after school (76.0%), difficulties with toilet training (47.9%) and speech articulation (52.3%), as well as elevated emotional problems (52.7%) and peer-related issues (46.4%), were prevalent. Most children received therapy (89.2%) but 59.1% of parents did not feel adequately supported to assist their child. Moreover, 37.5% of parents regularly took time off work to facilitate their child’s therapy attendance, while 49.1% had reduced their working hours or were contemplating doing so (16.7%). Parents expressed concerns about their child's future and well-being, with a prominent plea for guidance on supporting their child and increased awareness. Parents reported important strengths in their children, including empathy, creativity, cognitive abilities, perseverance, and good social and/or language skills. Conclusions These results highlight the significant impact of DCD from parents’ perspectives. The next step is to explore ways to empower and support parents, raise awareness, and collaborate with policymakers to address these challenges.